Primary cutaneous congenital leukemia reminiscent of epidermal nevus. - Forte, F.; La Forgia, N.; Santoro, N.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
A baby of Chinese ancestry was born in good health. Due to this reason he did not undergo any laboratory examination and was discharged as all the healthy newborns at the age of 48 hours. At birth he presented on the left nasal genal furrow a skin lesion diagnosed as epidermal nevus by the neonatologist. A pediatric dermatologist was consulted through a computerized advice. The skin lesion was a white, 3 cm long and 1 cm wide plaque, with circinate borders...